2023
DOI: 10.3389/fimmu.2023.1138077
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer analysis and experimental validation identify the oncogenic nature of ESPL1: Potential therapeutic target in colorectal cancer

Abstract: IntroductionExtra spindle pole bodies like 1 (ESPL1) are required to continue the cell cycle, and its primary role is to initiate the final segregation of sister chromatids. Although prior research has revealed a link between ESPL1 and the development of cancer, no systematic pan-cancer analysis has been conducted. Combining multi-omics data with bioinformatics, we have thoroughly described the function of ESPL1 in cancer. In addition, we examined the impact of ESPL1 on the proliferation of numerous cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Increasing evidence indicates that ESPL1 participates in cell cycle signalling in breast cancer [ 32 ], endometrial cancer (UCEC) [ 33 ] and HCC [ 11 ], thus promoting the proliferation and migration of cancer cells [ 14 ]. However, in terms of BC, the potential pathways in which ESPL1 is involved still need to be better defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that ESPL1 participates in cell cycle signalling in breast cancer [ 32 ], endometrial cancer (UCEC) [ 33 ] and HCC [ 11 ], thus promoting the proliferation and migration of cancer cells [ 14 ]. However, in terms of BC, the potential pathways in which ESPL1 is involved still need to be better defined.…”
Section: Discussionmentioning
confidence: 99%
“…Extra spindle pole bodies like 1 (ESPL1) are cysteine endopeptidases, and these proteins participate in several aspects of the cell cycle by activating segregase [ 10 ]. There is growing evidence that high expression of ESPL1 is strongly associated with the development of malignant tumours, such as hepatocellular carcinoma (HCC) [ 11 ], glioma [ 12 ], lung adenocarcinoma (LUAD) [ 13 ] and colorectal cancer (CRC) [ 14 ]. In addition, Chen et al found that the high expression of ESPL1 was associated with the occurrence and recurrence of BC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic kidney transplantation is the preferred treatment option for patients with end-stage renal disease, as it can signi cantly improve overall survival and quality of life [32]. However, graft rejection is a signi cant risk factor for long-term graft loss [5].…”
Section: Discussionmentioning
confidence: 99%